Rapid Prototyping for Design and Test of FPGA-Based Model Predictive Controllers for Power Converters - Purraji, Marziye; Zamiri, Elyas; Sanchez, Alberto; de Castro, Angel (Journal of electrical engineering & technology, 2025)
Recent advancements in FPGA technology have made these devices a cost-effective alternative for implementing Model Predictive Controllers (MPCs). This paper addresses the fast prototyping of FPGA-based Finite Control Set (FCS)-MPCs and the essential verification process preceding hardware-level testing. The methodology leverages MATLAB HDL Coder for automated HDL code generation. This approach offers a streamlined process and eliminates the need for expertise in hand-coded HDL, making it an ideal solution for power electronics engineers. The approach is exemplified using a three-phase active neutral point clamped converter. Beyond presenting the design approach, the paper introduces a systematic multi-stage verification process essential for the rapid prototyping of FCS-MPC controllers. This verification involves step-by-step simulations followed by experimental hardware-in-the-loop tests, ensuring the reliability of each stage for the smooth transition from pure simulation to FPGA hardware implementation of the controller. The proposed methodology not only simplifies the implementation and testing of the MPC algorithm within an FPGA but also facilitates the debugging process, a crucial aspect of the design phase.